To study impact of Brand Engagement on Customer Satisfaction for Flipkart E-Commerce Services Among People Living in Ahmedabad City - Viral Vijay Singh Jadoun; Bunty Kailash Dinodiya; Jignesh Vidani (MultiTech Publisher, 2024)
These Survey Results highlight the importance of brand engagement initiatives, such as social media campaignhs, email newsletters, loyalty programs, special offers or discount, and interactive content, in influencing customer satisfaction with flipkart's e-comerce services in ahmedabad city, Nonetheles, there is room for improvement to enhance overall satisfaction and make more effective use of features like augemented reality. The insights gained from this survey will assist flipkart in optimizing its brand engagement startegies and improving customer satisfaction among residents of ahmedabad City. This Survey also revealed that while flipkart augmented reality feature was rated neutral by half of the respondents (50%), approximately 48% reported using Flipkart pay Later. in terms of overall satisfaction with Flipkart's e comerce ssaervices, nearly half of the respondents expressed a neutral level of satisfaction (49.3%). Homever, approximately 54% of the respondents reported that Flipkart's brand engagement initiaves have positively influenced them, and 49.3 % stated their likehood to recommend Flipkart's services based on their brand engagement experiences. Over half of the respondents (52%) expressed their willingness to participate in a follow-up interview, indicating their interes in providing feedback and suggesting to improve Flipkart's e-commerce services.